2020
DOI: 10.1186/s12864-020-07279-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptomic analyses reveal the roles of secondary metabolism in the adaptive responses of Stylosanthes to manganese toxicity

Abstract: Background As a heavy metal, manganese (Mn) can be toxic to plants. Stylo (Stylosanthes) is an important tropical legume that exhibits tolerance to high levels of Mn. However, little is known about the adaptive responses of stylo to Mn toxicity. Thus, this study integrated both physiological and transcriptomic analyses of stylo subjected to Mn toxicity. Results Results showed that excess Mn treatments increased malondialdehyde (MDA) levels in leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…LOC101117953 is a retro-copy of PPP1CC (protein phosphatase PP1-gamma catalytic subunit gamma), which is not expressed in adult tissues as it lacks promoter region, and is thus less likely to be the causative gene for the tail phenotypes [ 8 ]. Previous studies also revealed that PDGFD is a likely causal gene for fat deposition in sheep tail, which promotes proliferation and inhibits differentiation of preadipocyte [ 11 , 31 33 ]. Two SNPs in PDGFD significantly affect the tail length and width [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOC101117953 is a retro-copy of PPP1CC (protein phosphatase PP1-gamma catalytic subunit gamma), which is not expressed in adult tissues as it lacks promoter region, and is thus less likely to be the causative gene for the tail phenotypes [ 8 ]. Previous studies also revealed that PDGFD is a likely causal gene for fat deposition in sheep tail, which promotes proliferation and inhibits differentiation of preadipocyte [ 11 , 31 33 ]. Two SNPs in PDGFD significantly affect the tail length and width [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided evidence of promising candidate genes influencing tail types based on single nucleotide polymorphism (SNP) markers [ 3 , 6 8 ]. However, the fat-tailed trait may be a contribution of multiple genes and have a complicated co-regulation mechanism [ 9 11 ]. DairyMeade and East Friesian are the two dairy breeds recently introduced to China with large frame, fast growth rate, lean carcass and typical thin tails.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed in a greenhouse at temperatures of 25 °C to 32 °C under natural sunlight with a photoperiod of about 13 h at the TCGRI, CATAS, Hainan, China (19°30′N, 109°30′E). Seeds were germinated for 3 d, and stylo seedlings were then transferred to a modified Hoagland nutrient solution containing 250 μM KH 2 PO 4 for 14 d as previously described [71]. After that, seedlings were separately transplanted into nutrient solution supplied with 0, 100 and 250 μM KH 2 PO 4 , which were regarded as low (Pi deprivation), moderate and high P supply treatments, respectively.…”
Section: Plant Growth and Treatmentsmentioning
confidence: 99%
“…Genes with q-value <0.05 and |log 2 (fold change)| ≥1 were assigned as differentially expressed. GO and KEGG enrichment analyses of DEGs were performed as previously described [71,76]. The interaction networks were analyzed by Cytoscape (version 3.8.0).…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…Using transcriptome analysis, a total of 2670 cadmium toxicity response genes were obtained in soybean roots [25]. A recent transcriptomic analysis in stylo leaves identified a total of 4094 responsive genes involved in Mn toxicity response [26]. However, transcriptome analysis on soybean response to Mn toxicity is rare.…”
Section: Introductionmentioning
confidence: 99%